A heterometallic nanosized tube Fe[(CN)6]2[Co(LN3O2)]3n and two of its lamellar polymorphous isomers. Issue 39 (18th September 2015) - Pan, F.; Gao, S.; Liu, H. Z.
Abstract : Polymorphous Fe–Co heterometallic crystals with interesting related structures based on the same sub-structures were prepared and studied. Abstract : Single crystals of three polymorphous compounds were synthesized started from two building blocks, [Fe(CN)6 ] 3− and [Co( L N 3 O 2 )] 2+ (L is a Schiff-base macrocyclic ligand derived from the condensation of 2, 6-diacetylpyridine with 3, 6-dioxaoctane-1, 8-diamine) using a crystallization condition control. All three compounds consist of electroneutral skeletons made up of Fe6 Co6 twelve-metal ring units, which is the smallest enclosed circle in their structures: 1 is comprised of 1D nanometer-diameter tubes possessing nanometer-sized tunnels (0.58 nm × 0.74 nm); 2 and 3 are based on piled-up 2D lamellar layers in the (6, 3) and (4, 4) networks, respectively. Magnetic studies indicate ferromagnetic interactions between cyanide-bridged cobalt(ii ) and iron(iii ) in each compound.